KEBIJAKAN CENSORSHIP TIONGKOK TERHADAP PERUSAHAAN MULTINASIONAL DALAM BIDANG ICT (INFORMATION COMMUNICATION TECHNOLOGIES) (STUDI KASUS GOOGLE INC.) - Muhammad Haikal Haikal (Global Political Studies Journal, 2019)
This study focuses on the impact of censorship policy implementation with Tiongkoknese government activities against Google Inc. in Tiongkok. The Tiongkoknese government has enforced strict censorship of google which is a multinational corporation with its main product of web-based search engine that provides information and news in general and is freely accessible to Internet users, but the information must be done first through a screening process conducted by the Tiongkoknese government, if the keyword in the input in the search engine service contains a negative view of the government, then the information will be in search is blocked by the Tiongkoknese government and disappear from google search.